2014
DOI: 10.1080/14681811.2014.909351
|View full text |Cite
|
Sign up to set email alerts
|

Primary schools and the delivery of relationships and sexuality education: the experience of Queensland teachers

Abstract: Primary school provides an appropriate opportunity for children to commence comprehensive relationships and sexuality education (RSE), yet many primary school teachers avoid teaching this subject area. In the absence of teacher confidence and competence, schools have often relied on health promotion professionals, external agencies and/or one-off issue-related presentations rather than cohesive, systematic and meaningful health education. This study examines the implementation of a 10-lesson pilot RSE unit of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(16 citation statements)
references
References 25 publications
(46 reference statements)
1
12
0
1
Order By: Relevance
“…This included publications that explored: the decisions and motivations of schools and external agencies to enter into educational partnerships 1,5,12 ; transitions of external agencies from extra-curricular activity provision to involvement in HPE lessons 24,26 ; the extent of reliance on external agencies to deliver HPE, 2,3,7,10,11,[14][15][16][17]22,27,28 and the preparedness of external providers to deliver highquality HPE in schools 9,23,25 or contribute to the professional development of teachers. 4 In addition, one publication mapped the services that are available to schools 13 and a number of articles sought to evaluate or critically engage with some of the 'solutions' that external agencies were providing.…”
Section: Research Focusmentioning
confidence: 99%
See 2 more Smart Citations
“…This included publications that explored: the decisions and motivations of schools and external agencies to enter into educational partnerships 1,5,12 ; transitions of external agencies from extra-curricular activity provision to involvement in HPE lessons 24,26 ; the extent of reliance on external agencies to deliver HPE, 2,3,7,10,11,[14][15][16][17]22,27,28 and the preparedness of external providers to deliver highquality HPE in schools 9,23,25 or contribute to the professional development of teachers. 4 In addition, one publication mapped the services that are available to schools 13 and a number of articles sought to evaluate or critically engage with some of the 'solutions' that external agencies were providing.…”
Section: Research Focusmentioning
confidence: 99%
“…single-sex students and coeducational), or school size, were only provided in eight articles. 2,3,[5][6][7]12,16,31 Of these, only two offered extensive commentary: one in the form of a table detailing the 'demographics of research population, sample and respondents', 5(404) and the other through a paragraph designed to exemplify the 'purposive sample of known characteristics in order to ensure that a diverse range [of schools] was chosen'. 16(2) It could be argued that this rich description should be provided in all articles, as the context will have significant implications for what influences supply of, demand for, and accessibility to, outsourcing services, and for how the reader interprets the data that have been generated through these studies.…”
Section: Selected School Setting and Participantsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in Australia, many teachers lack training and confidence to facilitate contemporary relationships and sexuality education (RSE). In primary schools, qualitative studies have observed a tendency for teachers to outsource puberty education29 30 and that less than half of the female teachers felt very confident in teaching menstruation 31. In primary and secondary schools, a lack of confidence has been noted in teachers to deliver RSE programmes 32 33.…”
Section: Introductionmentioning
confidence: 99%
“…Impediments upon teachers' confidence to deliver sexuality education have been widely documented. These include time constraints (Smith et al, 2011), lack of guidance regarding topics and depth of content (Johnson et al, 2014;Smith et al, 2013) and feeling as though other teachers did not value the work (Ollis and Harrison, 2016). A key component of teacher confidence is the extent to which teachers feel prepared to deliver content (Barr et al, 2014;Goldman and Coleman, 2013).…”
Section: Introductionmentioning
confidence: 99%